Length-weight relationships of sharks caught by artisanal fisheries from southeastern Brazil - Motta, F. S. [UNESP]; Caltabellotta, F. P. [UNESP]; Namora, R. C.; Gadig, O. B. F. [UNESP] (Wiley-Blackwell, 2014)
Presented are the length-weight relationships for eight shark species (Families Carcharhinidae and Sphyrnidae) caught by the small-scale fishery in southeastern Brazil, from July 1996 to December 2003.